LOAD ANALYSIS ON VERTICAL LIFTING OVERHEAD CONVEYOR STRUCTURES - Hakam, Muhamad; Wahidah, Hera Zulvi Fahriyatul; Hamzah, Fais (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Overhead conveyors are designed to facilitate the transfer of material from one location to another. One aspect that needs to be planned is the vertical lifting structure, which is the initial loading process the material is attached to the trolley at a higher level of overhead conveyor. By design this tool can facilitate material loading work, as it reduces the possibility of product damage, reduces risk of worker exhaustion and smoothest the production flow. Loading analysis is carried out using FEM-based software to determine the strength of structures on design concepts. Structural strength analysis recorded minimum safety factor is 3,928 at the end of the hoist profile, a maximum von misses stress value of 63,188 MPa at the target frame point of the long profile hoist and a limits displacement value of 0,238 mm on the loading rail. The results of the structural buckling analysis with a limit of 1 load on the design concept were 350,589 times the load.